DESIGNING AND TESTING OF SOLAR POWER PLANT FOR PARKING AREA AT ENGINEERING FACULTY UNIVERSITAS SAMUDRA - Mustafa Kamal; Taufan Arif Adlie; Nasruddin A. Abdullah; Fazri Amir (Fakultas Teknik Universitas Samudra, 2022)
Technological growth impacts all aspects of human life, from urban to rural. The increase in technological developments in all fields causes the need for electricity to continue increasing yearly, including in universities. The continuous use of electrical energy derived from fossil fuels has the potential to cause an energy crisis. The solution is to use renewable energy sources, such as solar energy, which is abundant and continuous. Solar energy is the energy obtained directly from solar radiation. It is the cleanest energy source that has been developed so far, making it a solution to solving the energy crisis. One way to utilize solar energy is by using solar cells. This study aims to analyze the use of solar power for electrical energy needed at the parking area of the engineering faculty building at Samudra University so that it can save energy and reduce electricity usage from PLN. The data collection process was carried out by measuring the current strength generated by the solar panels for 10 days. The results show an average voltage of 17.38 volts with 3 lamps loaded for 8 days. While without loading, the highest solar panel voltage results are found on Mondays and Thursdays with a voltage value of 12.7 after being charged, while the lowest solar panel voltage values are found on Sundays and Fridays with a voltage value of 12.3. After analyzing the data, the electricity requirement for a building is 792 KWh.